PVC gel smart sensor for robotics sensing applications: an experimental and finite element simulation study Montassar Aidi Sharif (M. A. S.) has a PhD degree in Electrical and Computer Engineering from Michigan State University (MSU) - USA. Currently, Dr. Sharif is with the Department of Electronic and Control Engineering and Computer Engineering Departments, Technical Engineering College—Kirkuk, Northern Technical University (NTU), Iraq - Sharif, Montassar Aidi (Engineering Research Express, 2022)
Research is now being done on soft electroactive polymers (EAPs), such as polyvinyl chloride (PVC) gel, as an example, for use in soft robotics and smart sensors. Although the sensing behavior of PVC gel has not yet been thoroughly investigated, it has been determined that this material reacts in some way to the stimuli that come from the outside. PVC gels are being utilized to construct a broad variety of different kinds of smart sensors due to the fact that their deformation may be endlessly configured by variations in electrode arrangement, applied mechanical stress, and the amount of plasticizer contained within the gel. In this study, experimental characterizations and the results of finite element simulations are discussed for a PVC gel compression sensor. The finite element simulation of what happens to PVC gel when it is compressed from the outside using mechanical force has been built using the COMSOL Multiphysics, which is a finite element simulation software. Additional experimental measurements of PVC gels are carried out in order to validate the underlying principles that have been presented thus far by providing context for the results of the simulations and to validate the findings effectively. Based on the findings, it appears that the suggested sensor is able to detect compression at a variety of amplitudes and rates . This study sheds light on the sensing capabilities of PVC gel in sensing investigations and provides a framework for conducting such investigations, thereby laying the groundwork for an increase in the use of PVC gel sensors in soft robotics research in the future.